2021
DOI: 10.1113/jp281834
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced slow inactivation contributes to dysfunction of a recurrent SCN2A mutation associated with developmental and epileptic encephalopathy

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The mother of Patient 48 carried a mosaic SCN2A variant R853Q with a ratio of about 20% in the peripheral blood. R853Q is a recurrent variation that has been reported repeatedly in the literature ( Ganguly et al, 2021 ). Both the Patient 48 and two other patients with the same variant in our study, as well as patients with the same variant reported in the literature, were diagnosed with West syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…The mother of Patient 48 carried a mosaic SCN2A variant R853Q with a ratio of about 20% in the peripheral blood. R853Q is a recurrent variation that has been reported repeatedly in the literature ( Ganguly et al, 2021 ). Both the Patient 48 and two other patients with the same variant in our study, as well as patients with the same variant reported in the literature, were diagnosed with West syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, R853Q patient iPSC-derived neurons showed no significant differences in electrophysiological properties at DIV 21, despite a LoF phenotype described in heterologous expression systems and in silico prediction of reduced neuronal firing (7,8,11). However, examination at an earlier (DIV 13-15) and later (DIV 28-31) time points revealed an increase in membrane capacitance and neuronal excitability at rest, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, patients with the de novo missense SCN2A variant R853Q present with late-onset (>3 months) seizures with neurodevelopmental delay are resistant to treatment with SCBs or other anti-epileptic drugs (4)(5)(6). A LoF has been reported as the principle biophysical mechanism for this variant (7,8,11).…”
Section: Introductionmentioning
confidence: 99%
“…S3). Population variants were chosen based on minor allele frequency greater than 0.0001 in gnomAD (19), while pathogenic variants were chosen to represent either gain-and loss-of-function effects based on previously published data (10,18,(20)(21)(22).…”
Section: Analytical Validity Of Automated Patch Clamp For Nav12mentioning
confidence: 99%